Providing Basic Needs and Encouragement as Strategies in Managing Aggression in Dementia Clients - Retno Lestari; Wendy Cross (Department of Nursing, Faculty of Medicine, Diponegoro University, 2013)
Purpose: The experiences of caregivers in managing dementia clients with aggressive behaviour have been an issue in nursing homes. This study utilized the fact that there is no significant strategy for managing aggression effectively. The aim of the study is to explore the experiences of caregivers in managing dementia clients with aggressive behaviour in nursing home in Jakarta, Indonesia.Method: This study employed a hermeneutic phenomenological approach so that caregivers were able to explore the phenomenon of aggression by dementia residents in the nursing home. Six experienced caregivers were interviewed in this study to uncover caregivers’ strategies they use in managing aggression in dementia residents.Result: The findings in this study were several strategies that have been used by caregivers to manage aggressive behaviour among dementia residents in the nursing home: providing basic needs and encouragement.Conclusion: The findings suggested caregivers to implement the strategies for managing aggression in dementia residents. Due to a limited number of related studies in Indonesia, this study recommended for further research to other nursing homes in Indonesia to determine if other strategies to manage aggression exist.